Analysis of the Impact of Learning with Online Media During the Covid-19 Pandemic on the Mental Health of Adolescent Through Literature Module - Benny Novico Zani; Siti Sholihat (Journal of World Future Medicine, Health and Nursing, 2023)
Online learning and working from home for educators are changes that must be made by lecturers to continue teaching students. Distance education has the aim of improving the quality of education and the relevance of education as well as increasing equitable access and expansion of education. Distance education that is held with good quality assurance and in accordance with the needs of stakeholders is one of the mechanisms for expanding access to higher education. Subjects and Methods: Systematic review using the database : Google Scholar. The search results that meet the criteria are then analyzed for articles. Results: Online learning has several impacts on students, namely (1) online learning still confuses students to become passive, less creative, and productive, (3) accumulation of information/concepts on students is less useful, (4) students experience stress, (5) increased students' language literacy skills. Conclusion: Online learning has several impacts on students. This can be prevented, one of them is by socializing literacy about the impact of using social media on mental health and academic performance through literacy modules with the aim that learning can be sought to be well received by students without reducing the essence of education itself.